Synthetic, spectrometric and computer modelling studies of novel ATP analogues - Gxoyiya, Babalwa Siliziwe Blossom (Rhodes University, Faculty of Science, Department of Chemistry, 2008)
This study has been concerned with the design and synthesis of A TP analogues with the potential to act as inhibitors of glutamine synthetase - a novel target for therapeutic intervention in the treatment of tuberculosis. Using a structural -analogy approach, various 3-indolylalkanoic acid, benzimidazole and pyrazolo[3,4-dJpyrimidine derivatives have been prepared and characterized. Alkylation of the heterocyclic bases using 4-(bromomethyl)-2,2-dimethyl-1 ,3-d ioxolane, 2-(bromomethoxy)ethyl acetate and 2-(chloroethoxy)ethanol in the presence of either NaH or BulOK afforded the corresponding N-alkylated derivatives of benzimidazole and 4-aminopyrazolo[3,4-dJpyrimidine (4-APP). Similar reactions with 3-indo lylalkanoic esters resulted in O-alkyl cleavage with the formation of new esters. Alkylation of benzimidazole with allyl bromide, 4-bromobutene and 2-methylbut-2-ene has also been shown to afford the corresponding l-alkenylbenzimidazoles in moderate to excellent yield (43-96%). Subsequent oxidation of these products using CTAP, gave the dihydroxy derivatives in poor to good yields (26-77%). Phosphorylation of various hydroxy derivatives of benzimidazole and 4-APP has been achieved using diethyl chlorophosphate to afford the corresponding monophosphate and 1,2-diphosphate esters. Glycosylation of each of the heterocyclic bases has been successfully achieved using 1,2,3,4,6-penta-O-acetyl-D-glucopyranose and SnCl4 in acetonitri le, while methanolysis of the resulting tetraacetates, using methanolic NaOMe, afforded the hydroxy derivatives in good yield (50-70%). Various 1- and 2-dimensional NMR spectroscopic methods (e.g., IH, 13C, lip, COSY, HSQC and HMBC) have been used to confirm the structures of the synthesized A IP analogues. The application of NMR prediction programmes has been explored, permitting assessment of their agreement with the experimental data and confirmation of assigned structures. High-resolution electron impact (EI) mass spectrometric data have been used to explore the mass fragmentation pathways exhibited by selected derivatives, and certain common fragmentations have been identified. Molecular modelling of selected products as potential glutamine synthetase ligands has been performed on the Accelrys Cerius2 platform, and interactive receptor-ligand docking studies have been conducted using the Ligand-Fit module. These studies have revealed possible hydrogen-boding interactions between the selected analogues and various amino acid residues in the glutamine synthetase active site.
Keywords: Spectrum analysis; Tuberculosis -- Treatment; Chemotherapy; Adenosine triphosphate; Adenosine triphosphate -- Synthesis; Adenosine triphosphate -- Computer simulation; Adenosine triphosphate -- Spectrometric imaging; Glutamine synthetase; Tuberculosis -- Chemotherapy